Resourcing Trust in a Fragmenting World: The Social-Economic Dimension and Relational Ethics in the Track of Böszörményi-Nagy - Meulink-Korf, Hanneke; Noorlander, Wim (European Journal of Mental Health, 2012)
In this essay, we combine literature on economics and social sciences, inducing practical experiences and philosophically and theologically inspired praxis. We give our perceptions of the recent fi nancial-economic crisis and the ‘free market’- economy and of some consequences in the private domain. As therapists we have to refl ect on contemporary issues of interrelatedness of social-economic facts and narratives with (inter)personal dimensions. How about the conditions for relational responsibility in the midst of social injustice and instability, hidden behind ideologies of autonomy and equality? Against this background as ‘heuristics of fear’, we search for a realistic perspective of hope. The strength of relational ethics can be seen as an illusion, when we would assume that being responsible is dependent on the extent of freedom which nature and culture give us. Although this assumption is familiar, relational ethics still are the motivational layer in which hope resides for repairing the hurt human justice. Reading Levinas helps us to understand how this is possible. The appeal of another person motivates me. His/her ‘command without force’ makes me free. In the contextual approach of Boszormenyi-Nagy, there still are valuable stepping stones to be found for resourcing the sense of responsible relational caring.